Decoding subject's own name in the primary auditory cortex. Issue 5 (27th December 2022) - Wu, Hang; Wang, Dong; Liu, Yueyao; Xie, Musi; Zhou, Liwei; Wang, Yiwen; Cao, Jin; Huang, Yujuan; Qiu, Mincong; Qin, Pengmin
Abstract: Current studies have shown that perception of subject's own name (SON) involves multiple multimodal brain regions, while activities in unimodal sensory regions (i.e., primary auditory cortex) and their interaction with multimodal regions during the self‐processing remain unclear. To answer this, we combined multivariate pattern analysis and dynamic causal modelling analysis to explore the regional activation pattern and inter‐region effective connection during the perception of SON. We found that SON and other names could be decoded from the activation pattern in the primary auditory cortex. In addition, we found an excitatory effect of SON on connections from the anterior insula/inferior frontal gyrus to the primary auditory cortex, and to the temporoparietal junction. Our findings extended the current knowledge of self‐processing by showing that primary auditory cortex could discriminate SON from other names. Furthermore, our findings highlighted the importance of influence of the insula on the primary auditory cortex during self‐processing. Abstract : We combined multivariate pattern analysis and dynamic causal modelling analysis to explore the regional activation pattern and inter‐region effective connection during the perception of subject's own name (SON). Our main finding showed that SON and other names could be decoded from the activation pattern in the primary auditory cortex. Our findings extended the current knowledge of self‐processing by showing that primary auditory cortex could discriminate SON from other names.